Value-Building Rather Than Risk-Reduction? Effects of TikTok Beauty Recommendation Videos on College Students’ Purchase Decisions - Li, Qiuyan; Zhao, Fengyu (Asia Pacific Economic and Management Review, 2026)
TikTok-style short-form video platforms have become an important channel for beauty product discovery and social commerce among young consumers. However, existing studies have mainly examined general video attributes such as informativeness, entertainment, and trust, while paying less attention to beauty-specific content characteristics and the comparative roles of perceived value and perceived risk. This study examines how three content characteristics of TikTok beauty recommendation videos - professionalism, authenticity, and practicality - influence college students’ purchase decisions. Drawing on the stimulus-organism-response framework, the study argues that these content characteristics affect purchase decisions through perceived value and perceived risk, while consumption values may further shape these relationships. A questionnaire survey was conducted among Chinese college students who had watched beauty recommendation videos on Douyin, the Chinese counterpart of TikTok, and the data were analyzed using reliability and validity tests, correlation analysis, regression analysis, mediation analysis, and exploratory moderation analysis. The findings show that professionalism, authenticity, and practicality all positively influence purchase decisions. Perceived value plays a significant mediating role, whereas perceived risk does not show a significant mediating effect. Additional analysis indicates that hedonic consumption values strengthen the effect of professionalism on perceived value but weaken the effect of authenticity on perceived value. The study contributes to short-form video marketing research by refining beauty-related content characteristics and by showing that value-building is a more important mechanism than risk-reduction in this social commerce context.